Prestige or Function? A Study of Intention to Buy Luxury Brands in Indonesia - Teresia Debby; Atik Aprianingsih; Agus Hasan Pura Anggawidjaja; VJ Wisnu Wardhono; Kaustubh Virkar (Media Ekonomi dan Manajemen, 2024)
This study explores the relationship between hedonic and functional value toward the intention to buy luxury brands as direct effects and through attitude toward luxury brands. This study used a survey to gather data from 113 respondents with birth years between 1981 and 2012 who had purchased luxury brands. This study used the partial least squares structural equation modelling (PLS-SEM) to evaluate the model and hypotheses. The result shows that hedonic value positively and significantly affects the intention to buy luxury brands. In addition, the result shows a positive relationship between hedonic value and intention for luxury brand purchases through attitude towards luxury brands. Functional value positively affects the intention to buy luxury brands. Meanwhile, functional value does not significantly affect attitude toward luxury brands. Furthermore, attitude toward luxury brands has a significant effect on the intention to buy luxury brands. Understanding these relationships can help marketers develop effective strategies to attract and retain consumers of luxury brands.